TATA KELOLA PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF DAN MENYENANGKAN (PAIKEM) DI SMA PONDOK PESANTREN IMMIM MAKASSAR - Burhanuddin, Azhar (Idaarah: Jurnal Manajemen Pendidikan, 2017)
From the results of research on the impact of PAIKEM is sure to help teachers in teaching and learning activities, because teachers are not too difficult in delivering materials and teachers enjoy in learning because students are active, students are directed to more creative develop creativity, teachers only more assess the results of student performance. Impact PAIKEM for Students, they feel more comfortable, friendly, easier for them to channel talent, easier to absorb the lesson because of this exciting atmosphere turned out to be more attention from the teacher who educates them. In line with the above statement, From the results of the research suggests that the positive impact of PAIKEM ie students will vigorously follow the teaching and learning activities because creative teachers create an atmosphere that students are actively creative, so it can make students confidently appear in front of the public.